Robust Cluster Building Unit: Icosanuclear Heteropolyoxocopperate Templated by Carbonate. Issue 51 (6th November 2015) - Liu, Fu‐Ling; Kozlevčar, Bojan; Strauch, Peter; Zhuang, Gui‐Lin; Guo, Ling‐Yu; Wang, Zhi; Sun, Di
Abstract: The encapsulation of carbonate derived from atmospheric CO2 has resulted in an icosanuclear heteropolyoxocopperate, isolated as a metal–organic 1D chain, 2D sheet, or 3D framework, in which the Cu20 nanocluster represents the first eight‐capped α‐Keggin polyoxometalate with the late‐transition‐metal Cu II as the polyatom, CO3 2− as the heteroanion, and OH − and suc 2− or glu 2− (H2 suc=succinic acid; H2 glu=glutaric acid) as the terminal ligands, which suggests a conceptual similarity to classical polyoxometalates. Even in the presence of competitive SO4 2− in the assembly system, the CO3 2− anion is still captured as a template to direct the formation of the Cu20 nanocluster, which indicates the stronger templation ability of CO3 2− compared with SO4 2− . When other aliphatic dicarboxylates, such as glutaric acid, were used as ligands, the CO3 2− ‐templated Cu20 nanocluster was maintained and acted as a cluster building unit (CBU) to be linked by two glutarate bridges to generate a distinct 1D metal–organic chain. This report presents not only a rare example of a huge anion‐templated transition‐metal cluster, but also its use as a robust CBU to construct novel coordination architectures. Variable‐temperature magnetic susceptibility studies revealed that an antiferromagnetic interaction exists within the Cu20 nanocluster. The correlation between the coordination structure and the electron paramagnetic resonance spectra recorded of both powder and single‐crystal samples are discussed in detail. Abstract : Cu20 nanocluster : A novel icosanuclear copper(II) nanocluster templated by carbonates (see figure) derived from atmospheric CO2 features an eight‐capped α‐Keggin polyoxometalate and serves as a robust cluster building unit (CBU) for the construction of novel coordination architectures.